Inferior frontal gyrus gray matter volume is associated with aggressive behavior in schizophrenia spectrum disorders. (30th August 2019) - Schoretsanitis, Georgios; Stegmayer, Katharina; Razavi, Nadja; Federspiel, Andrea; Müller, Thomas J.; Horn, Helge; Wiest, Roland; Strik, Werner; Walther, Sebastian
Highlights: GM matter volume in left inferior frontal gyrus related to MOAS total scores. Verbal aggression was associated with GM volume in left inferior frontal gyrus. Inhibition control and/or formal thought disorders may relate to aggression. Abstract: We aimed to assess potential gray matter (GM) alterations for aggressive patterns of behavior in a sample of in- and outpatients with schizophrenia spectrum disorders. Eighty-four patients previously participating in brain volumetric studies were included. Aggression was assessed using the Modified Overt Aggression Scales (MOAS) based upon review of clinical records of the hospital register. Multiple regression analyses for total MOAS and each MOAS subscale separately were conducted correcting for age, sex, history of addiction, chlorpromazine equivalents, illness duration, and total intracranial volume. Significant effects were reported in two cases; the total MOAS scores and MOAS verbal aggression scores were associated with GM volume in left inferior frontal gyrus. From the demographic/clinical characteristics, only the number of episodes correlated with the subscales and the total MOAS scores. Our results highlight the role of GM volume in left inferior frontal gyri in patients with history of aggression. This evidence ties in well with previous data reporting involvement of these regions in response control and semantic networks.